Textual range of linguistic variants in the direct transmission of the nineteenth-century Cuban novel Historia de un bribón dichoso - Santos Gallardo, Aliney (Espergesia, 2025)
Quite a few philologists have warned about the alteration of modern texts during their transmission, despite these materials being fixed and legitimized by print. Given that contemporary society relies substantially on its written testimonies, this constitutes a matter of significant interest for the preservation of peoples’ cultures. However, such variations are often attributed to normative language updates, stylistic flaws, or minor errata. Within the Cuban context, no studies are known to have investigated alterations in the transmission of national literature, excepting scarce critical editions—almost invariably approached through traditional methods and driven by descriptive rather than pragmatic interests. Addressing this research gap, and as partial outcomes of a broader study, this article aims to describe the textual scope of linguistic variants in the direct transmission of the novel Historia de un bribón dichoso. Employing a mixed-method approach that integrates quantifiable criteria and qualitative interpretation of analytical categories, this descriptive research adopts content analysis methodology. This approach examines both the textual surface and the implicit framework of the deep textual structure to draw valuable inferences. The results reveal significant alterations at multiple levels of the work’s textual structure. This study demonstrates that, despite the relative recentness of the regional literary heritage, its transmission history exhibits substantial alterations of scholarly relevance.